The Impact of Digital Finance on Total Factor Productivity of Enterprises - Xu, Xinyu (BCP Business & Management, 2022)
As a new financial service mode integrating traditional finance and technology, digital finance has an important impact on the high-quality development of micro enterprises. Based on the relevant data of China’s A-share listed companies from 2011 to 2019, this paper empirically tests the impact of digital finance on total factor productivity. The research finds that: (1) Digital finance is significantly positively correlated with total factor productivity of enterprises, that is, digital finance can improve total factor productivity of enterprises; (2) The mechanism test shows that the development of digital finance can effectively reduce the degree of financial mismatch and promote technological innovation of enterprises, so as to improve the total factor productivity of enterprises; (3) After analyzing the heterogeneity of individual characteristics of enterprises, it is found that when enterprises are under low government control, high financing constraints, and enterprises are high-tech enterprises, the role of digital finance in promoting total factor productivity of enterprises will be more significant. The research conclusion provides a certain reference basis for improving the quality and efficiency of financial services in the real economy, total factor productivity of enterprises and promoting the high-quality development of China’s economy.